Painter X for Photographers - Addison, Martin (Routledge, 2012)
Whether you are just starting out with Painter, or are a seasoned pro who wants to take your photographs to the next level, you can't go wrong with this essential guide by your side! Covering Painter X, but also applicable to earlier versions and to both PC and Macintosh users, this reader friendly book and DVD package will show you how to get the most out of this powerful program. Uniquely written specifically for photographers, Martin Addison gives a complete overview of the program, showing how to master each exciting tool, including the brand-new RealBristle and Smart Stroke brush libraries. Two all-new portraiture chapters show you how to turn photographs of your family members or professional clients into works of art ideal for framing. You'll be able to give all of your precious photographs the painterly touch in no time! Be sure to visit the accompanying website www.painterforphotographers.co.uk to view even more images and information to get you started! Pictures by Martin and Doreen Addison can be seen on their website: www.martinanddoreen.co.uk.